Total Reflection Metasurface with Pure Modulated Signal. Issue 14 (9th December 2018) - Chen, Lianwei; Li, Yang; Hong, Minghui
Abstract: Metasurface has been proposed as one critical platform for orbital angular momentum (OAM) multiplexing. While metasurfaces have unique advantages to achieve light modulation with an ultrathin 2D layer, the relatively low transfer efficiency is a primary drawback. Such weakness leads to the mixing of unmodulated light into the output signal and greatly limits the functionality. A new design strategy is presented to fabricate self‐filtering metasurface with pure signal light, which is computationally and experimentally verified on different applications, and it is also insensitive to the incident light polarization. Normal metasurface system requires bulky polarizer and filter, while our ultrathin design paves the way to multifunctional metasurface‐based chip‐scale circuits to replace the conventional bulky optical components. A proof‐of‐principle meta‐cavity is designed to improve the transfer efficiency by 83%, while theoretical calculation shows 633% enhancement for an upgraded setup. This design can be widely applied to OAM optics, integrated photonics, optical sensing, data processing, and nanoimaging. Abstract : The transfer efficiency of the metasurfaces cannot match the conventional optical components, which greatly limits the functionality. A new total reflection metasurface is proposed. It can eliminate the primary source of noise from unmodulated light, improve the efficiency by 633% theoretically, insensitive to polarizations, and "plug‐to‐use" as ultrathin components without extra bulky component.